The Practice of Cooperation Agreements for Micro, Small, and Medium Enterprises on the Shopee Marketplace from the Perspective of Sharia Economic Law - Rahmi Nur Azizah Nur Azizah (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2026)
The core problem of this research is how Sharia Economic Law views the practice of cooperation agreements for Micro, Small and Medium Enterprises on the Shopee Marketplace. The aim of this research is to find out and examine the practice of cooperation agreements for Micro, Small and Medium Enterprises on the Shopee Marketplace in terms of sharia economic law.The type of research used is field research using a qualitative approach, namely describing phenomena that occur in the field according to existing reality. The research location is in Tanah Datar Regency. The primary data source that the author uses is through interviews with MSME actors in Parak Juar. The data collection technique is by conducting interviews and documentation. The data analysis technique that the researcher carried out was qualitative analysis in order to collect data sources related to the problem being studied. The cooperation agreement between MSMEs and the Shopee marketplace regulates the rights and obligations of both parties in running an online business, in the form of an obligatory agreement and subject to the Civil Code (KUHPerdata). MSMEs are obliged to provide products, maintain quality and arrange delivery of goods, while Shopee provides the platform, payment system and technical support. The contract used in this collaboration is the ijarah bi al-manfa'ah agreement, where Shopee leases digital platforms and services to MSMEs. In practice, although Shopee provides various facilities that support MSMEs, such as promotions and training, there are challenges related to transaction uncertainty, such as problems with products that do not match orders or delivery. This shows that even though this collaboration is permitted under sharia law, it is important to ensure that transactions are still carried out in accordance with sharia principles, by prioritizing honesty, transparency and fulfilling the obligations of each party.